BLOW FLIES (DIPTERA : CALLIPHORIDAE) COLLECTED FROM NORTH-WESTERN REGION INCLUDING TWO NEW RECORDS FROM INDIA - SIDHU, INDERPAL. SINGH; SINGH, DEVINDER (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2002)
Twenty species of blow flies have been collected from north-west India covering the states of Punjab. Haryana. Himachal Pradesh, Delhi, Uttranchal and Rajasthan. One species represents its first report from Oriental region while another has been recorded from India for the first time.